2022
DOI: 10.1017/wet.2022.22
|View full text |Cite
|
Sign up to set email alerts
|

Multiple resistance to imazethapyr, atrazine, and glyphosate in a recently introduced Palmer amaranth (Amaranthus palmeri) accession in Wisconsin

Abstract: The continued dispersal of Palmer amaranth can impose detrimental impacts to cropping systems in Wisconsin. Our objective was to characterize the response of a recently introduced Palmer amaranth accession in southern WI to postemergence (POST) and preemergence (PRE) herbicides commonly used in corn and soybean. Greenhouse experiments were conducted with the WI putative herbicide-resistant accession (BRO), and two additional control accessions from Nebraska, a glyphosate-resistant (KEI2) and a glyphosate-susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…High-level resistance to foliar applications of fomesafen has been recently confirmed in a giant ragweed population from Wisconsin (Faleco et al 2021), though the characterization of the resistance mechanism is limited thus far. Fomesafen is a diphenylether herbicide that inhibits the PPO enzyme.…”
Section: Giant Ragweed Efficacy: Sequential Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-level resistance to foliar applications of fomesafen has been recently confirmed in a giant ragweed population from Wisconsin (Faleco et al 2021), though the characterization of the resistance mechanism is limited thus far. Fomesafen is a diphenylether herbicide that inhibits the PPO enzyme.…”
Section: Giant Ragweed Efficacy: Sequential Experimentsmentioning
confidence: 99%
“…Overall, these results demonstrate that mesotrione can be more effective than many existing soybean herbicides for preemergence control of multiple-resistant giant ragweed. A survey of giant ragweed infestations in Indiana indicated that biotypes susceptible to ALS inhibitors outnumber resistant biotypes in nearly half of ALS-R populations (Harre et al 2017), and only one instance of resistance to PPO inhibitors has been reported globally (Faleco et al 2021), though not yet confirmed in a published research article. Mesotrione, cloransulam, and fomesafen can all contribute soil-residual control of giant ragweed populations that are segregating for resistance, which is important for managing weeds throughout the critical weed-free period of soybean.…”
Section: Giant Ragweed Efficacy: Sequential Experimentsmentioning
confidence: 99%
“…The low degree of waterhemp control provided by the PRE herbicide premix flumetsulam þ clopyralid and atrazine may be related to waterhemp resistance to herbicides that inhibit acetolactate synthase (ALS) (Faleco et al 2022b) and photosystem II (PS II), respectively (Faleco et al 2022a(Faleco et al , 2022b. ALS-and PS IIresistant waterhemp has been widely reported across the midwestern United States (Evans et al 2019;Heap 2022;Vennapusa et al 2018).…”
Section: Waterhemp Controlmentioning
confidence: 99%
“…The use of herbicides with effective soil residual activity applied PRE provides an extended period of early season weed control, protecting crop yields during their most vulnerable developmental stages from weed interference (Grint et al 2022b; Oliveira et al 2017a). PRE herbicides can reduce the weed density and delay the time to POST applications, thus lowering the selection pressure for further resistance to POST herbicides (Faleco et al 2022a; Oliveira et al 2017b). Including PRE herbicides as part of an integrated weed management program brings more diversity to effective sites of action (SOAs) and opportunities for broad-spectrum chemical weed control (Norsworthy et al 2012; Somerville et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research reported that newly introduced A. palmeri populations in the United States, Brazil, Turkey, and South Africa were confirmed to be MHR (Faleco et al 2022;Küpper et al 2017;Mennan et al 2021;Reinhardt et al 2022). Wisconsin researchers reported a recently discovered A. palmeri population was threeway MHR and survived labeled rates of imazethapyr, glyphosate, and atrazine (Faleco et al 2022).…”
Section: Introductionmentioning
confidence: 99%